Assessing the ICC Office of the Prosecutor’s new policy on complementarity and cooperation: limitations in legal rigor in integration of alternative resolution mechanisms - Bezabh, Abebe Bahiru (Frontiers in Political Science, 2025)
This article examines the International Criminal Court (ICC) Office of the Prosecutor’s new policy on cooperation and complementarity concerning Alternative Resolution Mechanisms (ARMs) within the Rome Statute framework. Although the ICC aims to address serious international crimes, its inflexible stance limits effective collaboration with ARMs like Truth and Reconciliation Commissions, which are vital for transitional justice in conflict settings. Despite the intention behind the new policy, it fails to offer a fresh perspective. The article emphasizes the necessity for inclusive cooperation that recognizes the diverse nature of justice. It argues that the test of complementarity still overlooks interactions with ARMs, often marginalizing domestic mechanisms. Ultimately, the article advocates for a constrictive legislation and institutional establishment that aligns international law with local realities to promote peace, accountability, and stability worldwide.